Co-ordination of Health Services Liverpool : Child Welfare
1928-03 1928 1920s 6 pages -3- CO-ORDINATION OF HEALTH SERVICES W. RIDING OF YORKS. COUNTY MEDICAL OFFICER'S DEPARTMENT. Some idea of the work of the County Public Health Department may be obtained from the following. Since the year 1900 the Legislature has placed on County Councils numerous new duties relating to Public Health, notably the Medical Inspection of School Children and their treatment for minor ailments; Isolation Hospital Accommodation, the Treatment of Tuberculosis; the Treatment of Venereal Diseases; Maternity and Child Welfare; Housing, Milk Supply and Smoke Abatement. The Bacteriological Laboratory was opened in 1901, and since that date there has been constant extension in its work and scope. In 1902 the total number of specimens examined was 2,233, and in the year 1926 no less than 22,000 specimens passed through the Laboratory. The Milk and Dairies Act and Orders have added considerably to the work of County Councils, as regards the supervision of the milk supply, and examination of cows with the object of providing a clean milk supply free from tuberculosis. The quality of the milk supply also receives considerable attention, and in the County area our Food and Drugs Inpectors [Inspectors] submitted 2,081 samples of milk to the Public Analyst during 1926, and of this number 110 or 5.3% were found to be adulterated. In addition 1,535 other samples of food and drugs were examined, of which 55, or 3.6%, were adulterated. An interesting comparison may be made in the Vital Statistics relating to the Administrative County Area for the years 1900, 1910 and again for 1925 and 1926. Year. 1900 1910 1925 1926 Death Rate from all causes. 18.3 13.9 12.3 11.6. Infant Mortality Rate. 160 117 81 73 Phthisis. 1.1 0.79 0.70 0.62 The rates for the year 1926 are the lowest ever recorded for the West Riding Administrative County. The efforts made for the improvement of general sanitation, better housing conditions, and by concentrating on such specialised schemes of prevention as Child Welfare and Tuberculosis are reflected in the figures shown above. 292/824/1/119